A preliminary study of heart rate, SpO2, and temperature on portable non-invasive preemies car seat device (PreeCASE) for monitoring preterm infants - Muhammad Afiq Firdaus, Md Zin; Mohd Azrul Hisham, Mohd Adib (Springer Singapore, 2024)
Nowadays, with advanced technology, many parents choose to monitor their baby's health using a pulse oximeter device. However, the current device can be difficult for infants, particularly for preterm babies who require continuous monitoring after being discharged from the hospital. With the ever-evolving medical technology and the emphasis on non-invasive health monitoring, many parents now rely on pulse oximeter devices to keep track of their infant's health. In response to the challenges posed by existing devices, a new solution called the Preemies Car Seat Device (PreeCASE) has been introduced. This portable, non-invasive device along with a mobile application, aims to streamline monitoring of the heart rate, SpO2, and temperature for pretem infants. The PreeCASE device intergates an ESP32 microcontroller and state-of-the-art wireless network sensors to captures and relay the key parameters. It displays the data prominently on an LCD, reflecting the corresponding health levels. In addition to its monitoring capabilities, the PreeCASE device is designed to be lightweight and portable, similar to the convenience and innovation seen in artificial organ technology. This efficient and user-friendly device not only enhance the user experience but also provide a robust tool for pediatricians in Malaysia, promising a seamless transition and monitoring phase for preterm infants. This technological, advancement underscores the potential for future innovations in continuous health monitoring and care.